2012
DOI: 10.1149/2.018205jss
|View full text |Cite
|
Sign up to set email alerts
|

Influence of O2Gas on Etch Profile of Magnetic Tunnel Junction Stacks Etched in a CH4/O2/Ar Plasma

Abstract: The etch characteristics of magnetic tunnel junction (MTJ) stacks patterned with W/TiN films were examined using an inductively coupled plasma of a CH 4 /O 2 /Ar gas mix. The effect of the O 2 concentration on the etch rate, etch selectivity and etch profile of the MTJ stacks was examined. The etch profile of the MTJ stacks in 60% CH 4 /Ar gas appeared to be the best. The addition of 10% O 2 gas in CH 4 /Ar gas led to an improved etch profile with less redeposition on the sidewall of the MTJ stacks. This was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…4,13 Recent studies have focused on developing etching processes that employ non corrosive gas mixtures containing C, H, O and N, such as CO/NH 3 , CH 3 OH/Ar, CH 3 OH/H 2 O, CH 4 /Ar and CH 4 /O 2 /Ar. [5][6][7][8][9][10][11][12] MTJ stacks etching in such non corrosive gas mixtures mainly proceeds via oxidation of metals in the MTJ stack that compose each layer, formation of a protective layer and ion bombardment, which enables moderate etch rates and good etch profiles without any post etch degradation of the MTJ stacks. However, the lack of chemically reactive species in the plasma chemistry that can produce volatile etch byproducts results in heavy sidewall redeposition under certain conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,13 Recent studies have focused on developing etching processes that employ non corrosive gas mixtures containing C, H, O and N, such as CO/NH 3 , CH 3 OH/Ar, CH 3 OH/H 2 O, CH 4 /Ar and CH 4 /O 2 /Ar. [5][6][7][8][9][10][11][12] MTJ stacks etching in such non corrosive gas mixtures mainly proceeds via oxidation of metals in the MTJ stack that compose each layer, formation of a protective layer and ion bombardment, which enables moderate etch rates and good etch profiles without any post etch degradation of the MTJ stacks. However, the lack of chemically reactive species in the plasma chemistry that can produce volatile etch byproducts results in heavy sidewall redeposition under certain conditions.…”
mentioning
confidence: 99%
“…However, previous studies reported the formation of a protective layer and oxidation of the etched material. [9][10][11] The improved etch profile is attributed to partial oxidation of the film, which allows easy sputtering of the oxide layer and formation of a protective layer on the sidewall. Owing to fast etch rates and good etch profiles, 25% CH 3 COOH was selected as the standard concentration for the investigation of the etch profile evolution as a function of time.…”
mentioning
confidence: 99%